Mitigating Flood Peak Discharge with Biopore Absorption Holes (BAH) to Reduce Surface Runoff: Case Study of the Tanralili Sub-watershed - Mansida, Amrullah; Gaffar, Farida; Zainuddin, Muh Amir (Jurnal Teknik Sipil, 2025)
Land use changes in the Tanralili Sub-watershed have profoundly impacted its hydrological dynamics, leading to increased surface runoff and shorter return periods for peak flood discharges. Currently, a significant portion of the area, 75.51%, is dedicated to mixed dryland and wetland agriculture, leaving only 24.49% under forest or grass cover, which has rendered much of the land critical. This research examines the effectiveness of Biopore Absorption Holes (BAH) in mitigating flood risks by enhancing infiltration and reducing runoff. Experiments were conducted on soils with moderate permeability (0.00178 cm/s), utilizing PVC BAH units measuring 10 cm in diameter and 100 cm in length, equipped with biopores of ?10 mm. These units were installed in parallel on a 0.23% slope and tested under various rainfall intensities (I2, I5, I10), determined using the Mononobe equation, while peak discharge was estimated with the Nakayasu Synthetic Unit Hydrograph (HSS Nakayasu). The results showed a 58.80% reduction in peak flood discharge and a 62.99% increase in infiltration. These findings underscore the potential of BAH as an eco-friendly solution for flood mitigation. Expanding the use of BAH on open lands is recommended to bolster watershed resilience and tackle the growing risks of flooding.